Transformation of Ulama as Communicators: Youtube as a Da'wah Channel - Novriyanto, Bambang; Utari, Prahastiwi; Satyawan, Agung (UIR Press, 2024)
In the digital era of the development of YouTube social media technology, there are many video contents available, one of which is Islamic da'wah content. The use of ulama in doing da'wah on YouTube is a process of transforming ulama as communicators in preaching. By using YouTube as a da'wah channel, there has been an indirect convergence of communication elements, resulting in a blur between ulama as communicators and connoisseurs of da'wah content on YouTube as communicants. The purpose of this study is to see the transformation of ulama as da'wah communicators on YouTube as da'wah channels. This research methodology is qualitative using literature studies that look at previous studies that use content analysis and opinion polls. The results of this study show that therefore, preachers in actualizing their da'wah must understand that the content and form of da'wah are inseparable parts, but can be distinguished in the concept of da'wah. While the characteristics, delivery strategies and methods of da'wah also have an important position in da'wah. With the interactivity facilitated by digital media, the boundary between communicators and communicants is getting thinner when communicating using YouTube media.